PENGEMBANGAN PROFESI GURU: MEMBANGUN PROFESI YANG BERMARTABAT DAN BERWIBAWA - Novarianing Asri, Dahlia (Jurnal Pendidikan, 2012)
The objective of this paper is to describe the teacher as prefession and development of teacher profession as honourable and respectable profession. Teacher profession is considered as profession if it fulfills some criteria: providing self-working based service, having strong comitment, qualification which based on knowledge and specific skill ownership got from long and tight training, providing service which is given seriously, getting payment from client, and being controlled by peer when acquiring the profession. Teacher profession development is done by increasing the teacherâs quality, improving the teacher training system, recruiting, certitificating, and improving teacher management system.Keywords: development, teacher profession, profession, teacher, honourable, respectable